Forecasting the potential distribution and niche of two similar gastropod species in South America: the intermediate host of schistosomiasis Biomphalaria glabrata and the invasive Melanoides tuberculata - Ribas, Luiz Guilherme [UNESP] (2025)
Forecasting the potential distribution of gastropod species with socio-environmental significance under current and future scenarios is crucial for controlling disease transmissions and biological invasions. In this study, ecological niche modeling was employed to predict the potential distribution and assess niche overlap of two problematic gastropod species in South America: the native species Biomphalaria glabrata, which serves as a vector for schistosomiasis pathogen, and the invasive Melanoides tuberculata. Our findings revealed overlapping environmental niches between native and invasive gastropod species, with the invasive species exhibiting broader environmental requirements. The distinct environmental niches of each gastropod species translate into unique potential distribution locations in geographic space, which remain largely unchanged across current and future climatic scenarios. Additionally, we provide evidence suggesting that utilizing the invasive species as a biological control for health-related species may not be advantageous without specific management strategies. Despite niche similarities, the invasive gastropod has the potential to spread to less ideal habitats for the native species. Hence, strategies to address both native and invasive mollusks should be formulated based on empirical evidence to mitigate environmental, ecological, and health concerns.